Ayacucho: The use of visual technologies as memory evocative and sense of belonging - Trinidad, Rocío E. (2019)
The article deals with the ways of using visual technologies, photography and video, to promote the city of Ayacucho as a tourist destination, an identity builder, reminiscent of memory and a sense of belonging to the city. Pay attention to the use, made for this purpose, of architecture as an image technology through which it seeks to produce temporary simulations and sentiment structures related to the colonial period. Argues that the identification and use of colonial aesthetics or not in the buildings of Ayacucho serves to establish social classifications, distinctions and exclusions among those who identify themselves as «huamanguinos» and «new huamanguinos». The article is divided into two parts. The first deals with the videos that promote Ayacucho as a tourist destination and the second with the use of photographs in exhibitions and social networks.